Morphological study of levator glandulae thyroidea in Bangladeshi cadaver - Sultana, Seheli Zannat; Khalil, M; Khan, MK; Shamim, R; Parveen, S; Ara, ZG (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):179-83. The abstract of this article is available on the PubMed website